An Analysis of the Effectiveness of Inventory Management in Improving Operational Efficiency - Vettyca Diana Saputri; Nevi Fitriani (Universitas Dehasen Bengkulu, 2026)
Working capital management is a crucial aspect of corporate financial management because it directly influences a company's liquidity, operational efficiency, and profitability. Effective management of current assets and current liabilities enables firms to maintain smooth business operations while maximizing financial performance. This study aims to analyze the role of working capital management in improving corporate profitability by examining the relationship between working capital efficiency and financial performance. The study adopts a quantitative research approach using secondary data collected from the published annual financial statements of selected companies over the observation period. The data are analyzed using descriptive statistics and multiple regression analysis to evaluate the effect of working capital management on corporate profitability. The findings indicate that efficient working capital management contributes positively to corporate profitability by improving cash flow, optimizing inventory levels, accelerating accounts receivable collection, and effectively managing accounts payable. In addition, an efficient cash conversion cycle is associated with higher profitability because it enables companies to recover invested funds more quickly and reduce reliance on external financing. The study concludes that effective working capital management is an essential strategy for enhancing operational efficiency, maintaining financial stability, and improving long-term corporate profitability. The findings provide practical implications for corporate managers, investors, and policymakers in developing financial management strategies that support sustainable business growth and value creation.